Fatores associados à duração do aleitamento materno no município de Belém/Pa. - GADELHA, Elida Cristina Bezerra (2023)
The objective of this research was to identify which factors would be related to the duration of breastfeeding in the city of Belém/PA. This is a cross-sectional descriptive study, with a quantitative analysis, with 119 mothers, over 18 years of age and residing in the city. Data collection was performed using a digital form created by the authors of the research and disseminated on social media, based on literature found and recommendations from health agencies. The research was approved by the Research Ethics Committee, under opinion nº 4.821.906. The predominant sociodemographic profile of the participants was brown women who had children with a mean age of 28.03 ± 6.57 years, married, with a graduate degree and family income ranging from 1 to 5 minimum wages, who breastfed exclusively until 6 months of age. life and full weaning at 2 years or more. Among the factors analyzed, statistical significance (p<0.05) was identified between return to work/study, use of a bottle, presence of taboos related to breast milk, appointments with a nutritionist, and duration of exclusive breastfeeding, indicating that these factors can be decisive for the success of breastfeeding, such results are important for the formulation of assertive public policies in the health care of children and nursing mothers.